A retrospective study of trends of malaria cases admitted in tertiary care hospital in a metropolitan city - Lohare, Basvaraj S.; Pol, Sujata; Tapare, Vinay S. (International Journal Of Community Medicine And Public Health, 2025)
Background: Malaria remains a significant public health challenge in India despite global progress, accounting for nearly half of the malaria cases in the WHO South-East Asia Region (SEAR). Although there has been a marked reduction in malaria incidence and mortality in recent years, local transmission patterns and demographic disparities continue to pose challenges. This study aims to analyze the year-wise trends, demographic distribution, and key indicators of malaria transmission at a tertiary care hospital in a metropolitan Indian city. Methods: A cross-sectional analysis was conducted using retrospective data from the Integrated Disease Surveillance Program (IDSP) cell at a tertiary care facility. Reported malaria cases from 2010 to 2018, diagnosed via peripheral blood examination or rapid diagnostic test, were included. Time-series modeling, logistic regression, Poisson regression, and ANOVA were employed to evaluate temporal trends, demographic factors, seasonal variation, and clinical outcomes. Results: A total of 10,492 malaria cases were recorded over nine years. Annual incidence declined markedly by 83%, from 3,016 cases in 2010 to 485 in 2018. The slide positivity rate reduced from 12.06% to 0.89%, while case fatality rate dropped from 2.72% to 0.20%. Male patients accounted for 78% of cases, indicating substantial gender disparity. Seasonal peaks persisted, particularly during the monsoon. Conclusion: The findings highlight a substantial decline in malaria burden and mortality, reflecting the effectiveness of control interventions. Nevertheless, the evident gender disparity and seasonal surges underscore the need for targeted public health interventions and continuous surveillance to ensure continued progress toward malaria elimination.